Culinary MSME Development for Employment Generation and Local Economic Growth: A Qualitative Case Study in Sorong City - Muhammad Zakir Naik H Bachtiar; Hasbiah Hasbiah; Karfin Karfin (CV. Ulil Albab Corp, 2026)
Unemployment remains a major problem in many developing regions, particularly in Eastern Indonesia, where local economic potential has not been fully transformed into sustainable employment. This study examines the role of culinary micro, small, and medium enterprises (MSMEs) in promoting economic growth and reducing unemployment in Sorong City. This research applies a qualitative case study approach. Data were collected through in-depth interviews, participatory observation, and documentation of five purposively selected culinary MSMEs based on business sustainability, local labor involvement, and use of local resources. Data were analyzed using thematic analysis with the Miles and Huberman model. The findings show that culinary MSMEs function not only as economic units but also as social agents that create community-based employment, particularly for housewives, youth, and individuals with limited access to the formal sector. Key strategies include product differentiation based on local culture, use of local raw materials, gradual production capacity improvement, early digital marketing adoption, and capacity building through training and self-learning. However, MSMEs still face challenges such as limited capital, weak managerial capacity, low digital literacy, restricted access to formal financing, regulatory complexity, and limited institutional support. Overall, culinary MSMEs are important instruments for inclusive and sustainable local economic development.